2017
DOI: 10.1136/bmjquality.u211571.w4730
|View full text |Cite
|
Sign up to set email alerts
|

Improving consent form documentation and introduction of procedure-specific labels in a district general hospital

Abstract: Informed consent is an important aspect in patient care. Failings in this area may result in patient dissatisfaction or litigation. The aim of this project was to assess our practice in consenting and institute changes to maintain best practice. A consecutive series of 140 patients undergoing elective and trauma procedures were randomly identified over a nine-month period. The consent forms were reviewed and the following information collected: patient/ consenter details, procedure, legibility, if copy was off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The goal of these resources was to provide a uniform approach to documenting risks, and their use has been shown to produce an improvement in quality of consenting (24). Similar bene ts were found when using pre-printed consent labels for consenting patients (7,25).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The goal of these resources was to provide a uniform approach to documenting risks, and their use has been shown to produce an improvement in quality of consenting (24). Similar bene ts were found when using pre-printed consent labels for consenting patients (7,25).…”
Section: Introductionmentioning
confidence: 84%
“…In order to reduce the variation in the admission and consenting process, several approaches have been evaluated, ranging from enhanced training to the use of procedure-speci c proformas (6) and consent stickers with pre-printed risks (7). Although these have demonstrated bene t, their usage remains limited and best practice is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prior data has demonstrated that many consent forms do not contain all of the required elements to facilitate patient understanding and retention [10-11]. Additionally, the development of procedure-specific labels and consent forms will be considered, as they have previously demonstrated improvement in consent form accuracy [12]. Furthermore, the implementation of electronic and interactive versions of these consent forms would improve both the accuracy of documentation and patient understanding/informed decision-making [13].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of these resources was to provide a uniform approach to documenting risks, and their use has been shown to produce an improvement in quality of consenting [24]. Similar benefits were found when using pre-printed consent labels for consenting patients [7,25].…”
Section: Introductionmentioning
confidence: 89%
“…In order to reduce the variation in the admission and consenting process, several approaches have been evaluated, ranging from enhanced training to the use of procedure-specific proformas [6] and consent stickers with pre-printed risks [7]. Although these have demonstrated benefit, their usage remains limited and best practice is still unknown.…”
Section: Introductionmentioning
confidence: 99%